APPLICATION OF THE RASCH MODEL TO TEST TOOLS IN THE ANALYSIS OF SURVEY DESIGN - Anggraini, Nini; Nabillah, Chantika; Dermawan Lonan, Herdi; Sain, Hartayuni (Parameter: Journal of Statistics, 2023)
The purpose of this study was to examine the instruments used to assess students' abilities in the designer analysis course of the statistics study program at Tadulako University. There were 90 students enrolled in this course, and the questions included 25 multiple-choice items related to survey design content. The test instrument for understanding the survey designer course was the subject of this study. The Rasch method, which is used to get fit items, is used. Winsteps software was used to carry out this analysis. In accordance with the Rasch model, the Winsteps program produced 23 items with an average value of 1.11 and -0.08 for MNSQ Outfit for person and item, respectively. In spite of the fact that the person's and the item's Outfit ZSTD values are 1.11 and 0.26, respectively, and despite the fact that the instrument's reliability, as measured by Cronbach's alpha, is 0.86, 23 of the 25 question items fit and 2 do not.